Light-induced protein dimerization by one- and two-photon activation of gibberellic acid derivatives in living cells - Schelkle, Korwin; Griesbaum, Tristan; Ollech, Dirk; Becht, Steffy; Buckup, Tiago; Hamburger, Manuel; Wombacher, Richard (Angewandte Chemie. International edition, 2015)
We developed a highly efficient system for light-induced protein dimerization in live cells using photo-caged derivatives of the phytohormone gibberellic acid (GA3). We demonstrate the application of the photo-activatable chemical inducer of dimerization (CID) for the control of protein translocation with high spatiotemporal precision using light as an external trigger. Furthermore, we present a new two-photon (2P)-sensitive caging group, whose exceptionally high two-photon cross section allows the use of infrared light to efficiently unleash the active GA3 for inducing protein dimerization in living cells.
Gesehen am 18.06.2020